(untitled) (PerCursos, 2024)
Can school be considered a “private” apparatus of hegemony? Based on this question, the objective of this text is to discuss, in the light of Gramscian reflections, the determination of the school as a space of civil society, seeking answers that highlight, on the one hand, Gramsci’s theoretical-methodological contributions to education today, and on the other, the political and pedagogical potential of these indications for the struggle of workers and subaltern groups to educate and direct themselves in life, aiming the achievement of a regulated and self-managed society by associated producers. The study was carried out through the systematic reading and interpretation of Gramscian writings, mainly the Gramsci’s Prison Notebooks, published in Brazil in six volumes by “Civilização Brasileira”. The terms and expressions coined by Gramsci while reflecting on the school and the “apparatus of hegemony” were extracted from the author’s text with a view to problematizing their meanings, which would not be possible without a respectful and conscious analytical treatment of both unity and organicity of your thinking. Thus, the statement that the school can be understood as an apparatus of political and cultural hegemony finds in Gramsci’s writings not only fruitful documentation, but also logical and historical evidence, although this assertion still needs to be deepened by researchers in the field of education, considering that, for Gramsci, there is a deep articulation among school, hegemony and politics.